1970
DOI: 10.13057/biodiv/d150113
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and use of ethnomedicinal plants in coastal Karnataka, India

Abstract: Bhandary MJ, Chandrashekar KR. 2014. Diversity and use of ethnomedicinal plants in coastal Karnataka, India. Biodiversitas 15: 89-93. A study was undertaken in Coastal Karnataka, a culturally and floristically diverse region between the Western Ghats and the Arabian sea in India, to document the diversity and uses of ethnomedicinal plants of the area. This study resulted in the documentation of ethnomedicinal uses of 342 species of plants belonging to 34 families. The dominant families of ethnomedicinal plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…The habitus of medicinal plants used by the people in the studied areas was dominated by herbs (34.78%), then followed by bush (32.6%), trees (28.26%) and grass (4.35%). This data is similar to the results of research on medicinal plants on the coast of Karnataka, India, which mostly uses herbs followed by trees, vines, and shrubs (Bhandary and Chandrashekar 2014). In making the jamu, the respondents used various parts of plant body including leaf (48%), rhizomes (24%), stems (10%), fruits (8%), seeds (6%), all parts of plants (2%) and flowers (2%).…”
Section: Habitus Plants Part and Processingsupporting
confidence: 80%
See 1 more Smart Citation
“…The habitus of medicinal plants used by the people in the studied areas was dominated by herbs (34.78%), then followed by bush (32.6%), trees (28.26%) and grass (4.35%). This data is similar to the results of research on medicinal plants on the coast of Karnataka, India, which mostly uses herbs followed by trees, vines, and shrubs (Bhandary and Chandrashekar 2014). In making the jamu, the respondents used various parts of plant body including leaf (48%), rhizomes (24%), stems (10%), fruits (8%), seeds (6%), all parts of plants (2%) and flowers (2%).…”
Section: Habitus Plants Part and Processingsupporting
confidence: 80%
“…It was found that 510 species had been used for traditional medicine, and the community passed orally the knowledge from one generation to another (Bussmann dan Douglas 2006). Another research in Karnataka, India revealed that 342 species were used for curing 42 diseases (Bhandary and Chandrashekar 2014). In the community of Azad Jammu, Kashmir, Pakistan, people used traditional plants for treatment of disease with the process of extraction for active ingredients or consumption of herbal drinks.…”
Section: Introductionmentioning
confidence: 99%
“…Zone 4 had Bruguiera sexangula, Ceriops decandra and exoecaria agallocha. The mangroves have good adaptation to reduce the sedimentation impacts and support the trapping directly, stabilize sediments, and reduce the substrate hydrodynamic exposure by the root systems [61], [62]. The best mangrove species to grow in this sedimentary lagoon are Sonneratia Caseolaris and Avicennia Marina.…”
Section: Figure 8 the Landscaping Of Mangrove Ecosystem In W-salmentioning
confidence: 99%
“…Several ethnic-medico-botanical reports are available from this area (Bhandary 2020;Bhandary and Chandrashekar 2001, 2003, 2011Bhandary et al 1995Bhandary et al , 1996Harsha et al 2003Harsha et al , 2006. As many as 342 species of plants have been reported to be used for various ethnomedicinal purposes by the different indigenous communities of this region (Bhandary and Chandrashekar 2014). However, the non-medicinal aspects of the ethnobotany of this area have not received any scientific attention so far.…”
Section: Introductionmentioning
confidence: 99%